2004
DOI: 10.1111/j.1475-4754.2004.00152.x
|View full text |Cite
|
Sign up to set email alerts
|

The Provenance of Red Figure Vases From Locri Epizephiri (Southern Italy): New Evidence by Chemical Analysis

Abstract: Thirty-nine samples of red figure pottery found at Locri Epizephiri were analysed for 18 chemical elements by inductively coupled plasma emission spectroscopy. The finds, dated from the end of the sixth to the fourth century BC , were assigned to Attic, Sicilian and Locrian workshops due to their style of execution. Prior to facing the archaeological questions, possible biases on sample classification due to variable firing conditions, or to alteration during burial, were investigated: the results supported th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
9

Year Published

2004
2004
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 15 publications
0
15
0
9
Order By: Relevance
“…Chemical characterization of archaeological materials is now routinely used to investigate the production and movement of goods in the past, and has been particularly effectively applied to studies of obsidian and pottery as well as to metals and glass (Arnold et al 1991;Burger et al 1994;Burger et al 1998aBurger et al , 1998bBurger et al , 1998cBurger 2000;Burger and Glascock 2000;Cecil 2004;Glascock et al 2007;Gliozzo and Memmi Turbanti 2004;Gratuze 1999;Kennett et al 2004;Kennett et al 2001;Mallory-Greenough et al 1998;Mirti et al 2004;Niedershlag et al 2003;Perez-Arantegui et al 1996;Shortland 2002;Tykot 1997;Vaughn and Neff 2004). Studies identifying the presence of non-local goods contribute to interpretations of long-distance trade and interaction in a wide geographical and temporal range of archaeological contexts.…”
Section: Geochemical Studies Of Ceramic Exchange In the Archaeologicamentioning
confidence: 99%
“…Chemical characterization of archaeological materials is now routinely used to investigate the production and movement of goods in the past, and has been particularly effectively applied to studies of obsidian and pottery as well as to metals and glass (Arnold et al 1991;Burger et al 1994;Burger et al 1998aBurger et al , 1998bBurger et al , 1998cBurger 2000;Burger and Glascock 2000;Cecil 2004;Glascock et al 2007;Gliozzo and Memmi Turbanti 2004;Gratuze 1999;Kennett et al 2004;Kennett et al 2001;Mallory-Greenough et al 1998;Mirti et al 2004;Niedershlag et al 2003;Perez-Arantegui et al 1996;Shortland 2002;Tykot 1997;Vaughn and Neff 2004). Studies identifying the presence of non-local goods contribute to interpretations of long-distance trade and interaction in a wide geographical and temporal range of archaeological contexts.…”
Section: Geochemical Studies Of Ceramic Exchange In the Archaeologicamentioning
confidence: 99%
“…The clasts may consist of one or more of the following types: crystalloclasts, lithoclasts, ceramoclasts and bioclasts (Ghergari et al, 1999;Ionescu and Hoeck, 2008). Chemical analyses have been used since several years in archaeometry to group and classify ancient ceramics, and for provenance studies (Yoon et al, 2001;Gliozzo and Memmi Turbanti, 2004;Mirti et al, 2004;Barone et al, 2005;Belfiore et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…It should be made clear that we are not saying that rare earth elements (REE) and other trace elements are not useful to this kind of characterisation; numerous studies have demonstrated their usefulness in the past [10,15,19,21]. As shown in this study, depending on the nature of the clay materials used to produce the ceramics, major elements can be as important as some trace elements, if not more so.…”
Section: Discussionmentioning
confidence: 76%